Asset management : transforming asset dependent businesses - Lloyd, Chris, 1959-; Corcoran, Michael (ICE Publishing, 2019)
With contributions from leading advisers, industry experts and academic researchers, Asset Management, Second edition is an essential reference on the practicalities of adopting asset management principles, methods and techniques. The book demonstrates how Asset Management can transform the prospects of infrastructure and asset dependent businesses, by reducing risks and costs, and generating increased value for shareholders and stakeholders. Fully updated, this second edition contains a collection of short, authoritative and multi-disciplinary contributions which together provide an accessible and comprehensive overview of asset management best practice that is applicable to all sectors.